1992
DOI: 10.1515/humr.1992.5.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Laughter and stress

Abstract: The effectiveness of laughter in reducing physiological and psychological measures of stress is compared with relaxation training and control groups. Personality factors of sense ofhumor and use ofhumor to cope äs well äs group size are also compared. Subjects were 74 College students randomly assigned to either a humorous or control videotape, or an audiotaped relaxation program. While laughter was not found to be äs effective äs relaxation training in reducing physiological measures of stress, it did appear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…This work is related to some very practical applications of humor in medical settings with the use, for example, of "clown doctors" (Buchanan 2000) and humor to reduce anxiety among patients (Astedt-Kurki and Liukkonen 1994). In a related manner, other studies have shown a relationship between humor and stress reduction and other types of coping behavior (Cann et al 1999;Lefcourt et al 1997;Lefcourt and Thomas, 1998;Martin 2006;Martin et al 1993;Nezlek and Derks 2001;White and Winzelberg 1992); work extended into organizational domains (Avtgis and Taber 2006;Fry 1995;Lefcourt et al 1995;Moran 1990;Moran and Massam 1997;Rosenberg 1991). There is considerable physiological and phenomenological evidence of the stress-reducing, palliative or coping contribution of humor.…”
Section: The Funny Function: Orthodox Functionalist Research On Humomentioning
confidence: 99%
“…This work is related to some very practical applications of humor in medical settings with the use, for example, of "clown doctors" (Buchanan 2000) and humor to reduce anxiety among patients (Astedt-Kurki and Liukkonen 1994). In a related manner, other studies have shown a relationship between humor and stress reduction and other types of coping behavior (Cann et al 1999;Lefcourt et al 1997;Lefcourt and Thomas, 1998;Martin 2006;Martin et al 1993;Nezlek and Derks 2001;White and Winzelberg 1992); work extended into organizational domains (Avtgis and Taber 2006;Fry 1995;Lefcourt et al 1995;Moran 1990;Moran and Massam 1997;Rosenberg 1991). There is considerable physiological and phenomenological evidence of the stress-reducing, palliative or coping contribution of humor.…”
Section: The Funny Function: Orthodox Functionalist Research On Humomentioning
confidence: 99%
“…Since then, some evidence indi-cates that laughter can ameliorate certain types of pain (e.g., Ref. [99]), may promote immune functions [43] and reduce some physiological and psychological stress responses [3,100], while enhancing feelings of well-being, in part by counteracting negative affects [41,93]. Some of these effects could be due to the release of endogenous opioids and oxytocin -neuropeptides that are known to be important in mediating social affect [16,34,55], but many other brain and body chemistries are likely to be involved [3].…”
Section: Clinical Implications Of This Work With a Focus On Adhd Addmentioning
confidence: 99%
“…He then argues that humor should be studied as an inherently social phenomenon) with the unit of observation being not the individual but rather the evocative transaction. TENSION RELIEF Humor's stress-reducing benefits are widely recognized (Dienstbier 1995;Lefcourt & Martin 1986;Martin & Lefcourt 1983;Schacter & Wheeler 1962;White & Winzelberg 1992). While empirical findings about the precise relationship between humor and stress remain complicated (e. g., Kuiper & Martin 1998) and controversial (see review in White & Winzelberg 1992) evidence does suggest that when aroused, individuals laugh more (Schacter & Wheeler 1962) and interpret humorous stimuli as more funny (Cantor) Bryant & Zillman 1974;Prerost & Brewer 1977).…”
Section: Definitions Of Humormentioning
confidence: 99%
“…While empirical findings about the precise relationship between humor and stress remain complicated (e. g., Kuiper & Martin 1998) and controversial (see review in White & Winzelberg 1992) evidence does suggest that when aroused, individuals laugh more (Schacter & Wheeler 1962) and interpret humorous stimuli as more funny (Cantor) Bryant & Zillman 1974;Prerost & Brewer 1977). Laughing appears to reduce psychological stress (White & Winzelberg 1992). Bales and Slater (1955) relate the tension-reduction functions oflaughter to the process of task-group interaction.…”
Section: Definitions Of Humormentioning
confidence: 99%